2017
DOI: 10.1128/aac.01364-16
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Doravirine-Atorvastatin Drug-Drug Interaction Study

Abstract: Doravirine is a novel, highly potent, nonnucleoside reverse transcriptase inhibitor that is administered once daily and that is in development for the treatment of HIV-1 infection. In vitro and clinical data suggest that doravirine is unlikely to cause significant drug-drug interactions via major drug-metabolizing enzymes or transporters. As a common HIV-1 infection comorbidity, hypercholesterolemia is often treated with statins, including the commonly prescribed atorvastatin. Atorvastatin is subject to drug-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…The results suggested no clinically relevant effects of doravirine on the PK of metformin and that dose adjustment of metformin is not required when coadministered with doravirine. The current data are consistent with previous in vitro studies 18 and clinical trials, 12,25,26,[31][32][33] which have suggested that doravirine is unlikely to be responsible for DDIs through its actions on metabolizing enzymes and transporters. Doravirine has been shown in in vitro/in vivo studies to be primarily metabolized via oxidative metabolism by CYP3A 17,18 and is also a substrate for P-glycoprotein (P-gp) in vitro 17 ; however, in vivo data suggest P-gp is unlikely to play a significant role in its absorption and elimination.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results suggested no clinically relevant effects of doravirine on the PK of metformin and that dose adjustment of metformin is not required when coadministered with doravirine. The current data are consistent with previous in vitro studies 18 and clinical trials, 12,25,26,[31][32][33] which have suggested that doravirine is unlikely to be responsible for DDIs through its actions on metabolizing enzymes and transporters. Doravirine has been shown in in vitro/in vivo studies to be primarily metabolized via oxidative metabolism by CYP3A 17,18 and is also a substrate for P-glycoprotein (P-gp) in vitro 17 ; however, in vivo data suggest P-gp is unlikely to play a significant role in its absorption and elimination.…”
Section: Discussionsupporting
confidence: 91%
“…Doravirine has been shown in in vitro/in vivo studies to be primarily metabolized via oxidative metabolism by CYP3A 17,18 and is also a substrate for P-glycoprotein (P-gp) in vitro 17 ; however, in vivo data suggest P-gp is unlikely to play a significant role in its absorption and elimination. 17 Furthermore, in vitro and clinical data demonstrate that doravirine has low potential to modulate CYPs 12,18,25,26 or major drug transporters, including the organic anion transporting polypeptide (OATP) 1B1/B3, breast cancer resistance protein (BCRP), organic anion transporter (OAT) 1/3, and organic cation transporter (OCT) 2. 18 Doravirine has been shown previously not to have a clinically meaningful effect on the PK of substrates of CYP3A, 12,25,26,[31][32][33] OATP1B1, 26,32 P-gp, 25,26,32 BCRP, 25,26,32 or uridine 5 -diphosphoglucuronosyltransferase 1A1/3/9.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous clinical trials in which doravirine has not been shown to be a perpetrator of DDIs as a concomitant partner with other medications. [18][19][20][21] The trial was conducted with methadone administered at steady state and doravirine administered for 5 days. The 5-day duration was selected because, based on the half-life of doravirine, steady-state concentrations were expected to be attained within 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…10 In one study, the half-life of the R-and S-forms of methadone was reported to be 37.5 and 28.6 hours, respectively. 14,15 To date, preclinical and clinical data suggest that doravirine has minimal drug-drug interactions (DDIs) [18][19][20][21][22] as doravirine is not expected to either induce or inhibit any of the major CYP enzymes or transporters. 14,15 Phase 2 and 3 trials in treatment-naïve HIV-1-infected adults have shown that doravirine in combination with other antiretroviral agents is noninferior in terms of efficacy, but also demonstrates a more favorable safety profile compared with other treatment regimens.…”
mentioning
confidence: 99%
See 1 more Smart Citation